Piperazine- and Piperidine-Containing Thiazolo[5,4-d]pyrimidine Derivatives as New Potent and Selective Adenosine A2A Receptor Inverse Agonists - Flavia Varano; Daniela Catarzi; Erica Vigiani; Fabrizio Vincenzi; Silvia Pasquini; Katia Varani; Vittoria Colotta (Pharmaceuticals, 2020)
The therapeutic use of A2A adenosine receptor (AR) antagonists for the treatment of neurodegenerative disorders, such as Parkinson and Alzheimer diseases, is a very promising approach. Moreover, the potential therapeutic role of A2A AR antagonists to avoid both immunoescaping of tumor cells and tumor development is well documented. Herein, we report on the synthesis and biological evaluation of a new set of piperazine- and piperidine- containing 7-amino-2-(furan-2-yl)thiazolo[5,4-d]pyrimidine derivatives designed as human A2A AR antagonists/inverse agonists. Binding and potency data indicated that a good number of potent and selective hA2A AR inverse agonists were found. Amongst them, the 2-(furan-2-yl)-N5-(2-(4-phenylpiperazin-1-yl)ethyl)thiazolo[5,4-d]pyrimidine-5,7-diamine 11 exhibited the highest A2A AR binding affinity (Ki = 8.62 nM) as well as inverse agonist potency (IC50 = 7.42 nM). In addition, bioinformatics prediction using the web tool SwissADME revealed that 8, 11, and 19 possessed good drug-likeness profiles.